Phytochemical Properties and Proximate Composition of Papaya (Carica papaya L. var solo 8) Peels - Martial-Didier, Adingra Kouassi; Hubert, Konan Kouassi; Jean Parfait, Kouadio Eugène; Kablan, Tano (Turkish Journal of Agriculture - Food Science and Technology, 2017)
Papaya (Carica papaya) is a common tropical fruit used for nutrition as well as medicinal purposes. Apart from fruit, seed, latex and other plant parts of papaya tree have been shown to have medicinal properties. Since, no systematic study has been performed on nutritional analysis of papaya (Carica papaya L. var solo 8) peels. In this study, the proximate composition, mineral element profile and phytochemical composition of papaya (Carica papaya L. var solo 8) peels were investigated. The peels were harvested fresh, dried in an oven at 45Â°C for 48 hours, ground and analyzed according to standard procedures. Proximate analysis showed high level of proteins (11.67 ± 0.04 %), crude fibre (32.51 ± 0.03 %), carbohydrate (47.33 ± 0.08 %), ash (5.98 ± 0.03 %) 0.03 %) and fat (2.51 ± 0.13 %). Mineral analysis indicated the papaya (Carica papaya L. var solo 8) peels were specifically rich in potassium and phosphorus. Potassium was found to be the most abundant mineral present in the peels (516.33 ± 0.82 mg/100g). Phytochemical composition showed high level of total phenolic (65.48 ± 0.39 mg (GAE)/100 g DW), flavonoids (5.58 ± 0.83 mg (QE)/100 g DW) and tannins (10.51 ± 0.93 mg (TAE)/100 g DW). The methanolic extracts of the papaya (Carica papaya L. var solo 8) peels exhibited the high DPPH radical scavenging activities (81.89 ± 0.14 %).These data indicated that this papaya (Carica papaya L. var solo 8) peels could constitute a potential good source of natural antioxidant for local population.